Inhibition by restricted-calorie diet of lymphoproliferative disease and renal damage in MRL/lpr mice. - Fernandes, G (1984)
Restriction of calorie intake from the time of weaning greatly prolongs life, and it inhibits development and expression of the lymphoproliferative syndrome, renal disease, and decline of certain immunologic functions with age in MRL/lpr mice. This dramatic influence of diet on mice of this short-lived autoimmunity-prone strain, while associated with decreased rate of growth, is not associated with debilitation or apparent disease in the MRL/lpr mice. The massive lymphadenopathy and splenomegaly that developed in the putatively well-fed animals was prevented by dietary restriction, as were histopathologic abnormalities of thymus, spleen, lymph nodes, and kidneys.